A Rare Case of Primary Heterotopic Meningioma of Nasal Cavity presenting with Right Eye Proptosis - Harlalka, Munmun; Kalita, Abhijit; Kalita, Lachit (Annals of Pathology and Laboratory Medicine, 2023)
Meningiomas are slow growing intracranial neoplasm of central nervous system accounting for 15% of all intracranial tumors. Rarely it appears extracranially, mostly in the head and neck region, and specifically in the sinonasal tract with variable clinical presentation. It can mimic various other malignancies which are common at a particular location. We present a case of a 26 year old female with progressive proptosis of the right eye and intermittent headache without any vision impairment for about three years. Radiological features showed an ill-defined solid-cystic lesion epicentred in right nasal cavity suggesting olfactory neuroblastoma. Histomorphological and immunohistochemistry assessment favoured a diagnosis of Transitional meningioma, WHO grade I. Awareness of primary heterotopic meningioma will help in early diagnosis and appropriate management of the patient, particularly while evaluating a case of sino-nasal mass.